Analysis of measured thermally induced rock deformation. (15th October 2020) - Pei, L.; Blöcher, G.; Milsch, H.; Zimmermann, G.; Zhang, H.; Li, X.; Huenges, E.
Highlights: Different temperatures affect the readouts of an extensometer. The gain of the extensometer-amplifier circuit develops in a heating test. The thermally induced axial and lateral rock deformation appeared to be isotropic. Abstract: In order to improve the accuracy of laboratory measurement of thermally induced rock deformation in a thermo-triaxial rock testing apparatus, the present study investigated the factors offsetting the readouts of the extensometers as applied for this measurement. Via conducting a calibration experiment heating an aluminum sample from 30 °C to 60 °C, it was observed that the expansion in the metallic parts built in the extensometers offset the measured sample deformation. Moreover, the heterogeneous temperature distributed in the extensometer-amplifier circuit yielded a varying pre-amplification coefficient. Such coefficient further reduced the measured deformation in the sample setup. A method was then developed quantifying the time (heating path)-dependent evolution of the pre-amplification coefficient and the reading offsets due to the expansion in the metallic parts. The applicability of this method was exemplified by correcting the deformation in a limestone sample as measured in a drained heating test. The so obtained coefficient of thermal expansion of the tested limestone was in accordance with the theoretical bounds, which validated the present correction method. Hence, our study could be referenced by laboratory investigations on thermally induced rock deformation using similar experimental setup and following defined heating paths.